Rbio: A tool for biometric and statistical analysis using the R platform - Bhering, Leonardo Lopes (Crop Breeding and Applied Biotechnology, 2017)
Rbio is a free software for data processing. It is compatible and integrated with the free R software, which is globally accepted for statistical analysis. Thus, Rbio takes advantage of all processing potential of the R software. However, this new software allows the user to perform all the analyses without knowing the programming in R language. Rbio is available in Portuguese; it can be downloaded from the Internet (http://www.biometria.ufv.br), and requires the Windows operating system. It has a set of sample files, making it easy to be used. Currently, it supplies the user with all scripts internally used to process the analyses. Rbio can perform descriptive statistics, analysis of variance, estimation of genetic parameters and means tests, multivariate analysis, nonparametric tests, regressions, correlations, biometrics, bioinformatics, and simulation.
Keywords: Software; Programming; Data analysis; Quantitative genetics; Biometrics